Experience and application prospects of a new technological level at the engineering collieries-of Ukraine - Lyashenko O.F.; Makarov V.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2003)
Experience in using of extraction a new technological level engineering of domestic and foreign manufacture at Ukrainian collieries in different mountain - geological conditions is analysed. The estimation of prospects of its application is executed.